Optimal design for flexible operation with multiple fluctuating input parameters - Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computer Aided Chemical Engineering)

Numerical analysis of conjugate heat transfer within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.; Inguva, Venkatesh (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Heat transfer enhancement with internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Rezension zu "Helmut Simon. Leben zwischen den Zeiten. Von der Weimarer Republik bis zur Europäischen Union - Vom Bauernbub zum Verfassungsrichter und Kirchentagspräsidenten" hg. von Becker, Peter; Simon, Heide - Breckner, Anne (Jahrbuch für Evangelischen Kirchengeschichte des Rheinlandes (JEKGR))

Schöpfung, Universität und Schule - Breckner, Anne

Bericht: Tagung des Arbeitskreises für historische Religionspädagogik: Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert - Breckner, Anne

Estimation of component reliability from superposed renewal processes by means of latent variables - Rodrigues, Agatha S.; Kerschke, Pascal; Pereira, Carlos Alberto De Bragança; Trautmann, Heike; Wagner, Carolin; Hellingrath, Bernd; Polpo, Adriano (Comput. Stat.)

Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung
Der Terminus Wissenstransfer hat in den letzten Jahren verstärkt an Bedeutung gewonnen. Er bezieht sich auf die Zirkulation von Wissen zwischen Systemen, Organisationen oder Parteien, etwa zwischen Hochschulen und Gesellschaft. Damit ist nicht ‚nur‘ der Transfer wissenschaftlicher Erkenntnisse in gesellschaftliche Kontexte gemeint, sondern vielmehr - über den Erwerb und die Weitergabe von Wissen hinaus - der Dialog und die Diskursbildung zwischen Wissenschaft und Gesellschaft. Der vorliegende Band nimmt dabei entstehende Aufgaben, Herausforderungen und Chancen kulturwissenschaftlicher Forschung in den Blick. Entgegen der Annahme, Projekte aus dem Feld der Kulturwissenschaften würden im Bereich des Abstrakten verbleiben, präsentiert er Beispiele kulturwissenschaftlicher Forschung, die Theorie und Praxis berücksichtigen sowie die Verzahnung von theoretischen Erkenntnissen und ihr Mitwirken an gesellschaftlichen Diskursen verdeutlichen.

Romane der Wendeliteratur als Medien des Wissenstransfers. Eine Anstiftung zum Gespräch - Heerdegen, Björn (Wissenstransfer: Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Digitalisierte Arbeitsprozesse im Hotel- und Gastgewerbe konkret: (Digitalisierungs-) Potenziale und Kompetenzanforderungen an Auszubildende - Meyer, Anja; Kirchhof, Johanna (HiBiFo – Haushalt in Bildung & Forschung)
Digitalisierte Arbeitsprozesse als Lerngegenstand dienen als Ausgangspunkt der für die Aufgabenbewältigung notwendigen Kompetenzen. Am Beispiel der Planung und Durchführung einer Veranstaltung in der Hotellerie sollen Digitalisierungspotenziale aufgedeckt und notwendige Kompetenzen zum Umgang mit diesem Arbeitsprozess herausgearbeitet werden.

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

The Influence of Electrode Indentation Rate on LME Formation during RSW - Böhne, Christoph; Meschut, Gerson; BIEGLER, MAX; RETHMEIER, MICHAEL (Welding Journal)
During resistance spot welding of zinc-coated advanced high-strength steels (AHSSs) for automotive production, liquid metal embrittlement (LME) cracking may occur in the event of a combination of various unfavorable influences. In this study, the interactions of different welding current levels and weld times on the tendency for LME cracking in third-generation AHSSs were investigated. LME manifested itself as high-penetration cracks around the circumference of the spot welds for welding currents closely below the expulsion limit. At the same time, the observed tendency for LME cracking showed no direct correlation with the overall heat input of the investigated welding processes. To identify a reliable indicator of the tendency for LME cracking, the local strain rate at the origin of the observed cracks was analyzed over the course of the welding process via finite element simulation. While the local strain rate showed a good correlation with the process-specific LME cracking tendency, it was difficult to interpret due to its discontinuous course. Therefore, based on the experimental measurement of electrode displacement during welding, electrode indentation velocity was proposed as a descriptive indicator for quantifying cracking tendency.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Reduction of flange widths in resistance spot welding by application of eccentric electrode cap geometries - Böhne, Christoph; Meschut, Gerson (Welding and Cutting)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Untersuchung der Charakterisierung der Partikelform und deren Einfluss auf die Fließfähigkeit - Goncz, Nico; Ponusamy, SathishKumar

Untersuchung eines neuen dynamischen- mechanischen Partikelverrundungsprozesses (Studienarbeit) - Keksel, Ewald; Ponusamy, SathishKumar

Untersuchung der Polymer-Zerkleinerung in einer Kryo-Prallmühle (Studienarbeit) - Almohammad, Ahmad; Ponusamy, SathishKumar

Digitalisierungsbezogene Fortbildung und professionelle Lerngelegenheiten von Lehrpersonen der Sekundarstufe I in Deutschland und im Bundesländervergleich - Eickelmann, Birgit; Lorenz, R.; Endberg, M.; Domke, Marius (Schule digital – der Länderindikator 2021. Lehren und Lernen mit digitalen Medien in der Sekundarstufe I in Deutschland im Bundesländervergleich und im Trend seit 2017)